Origin of high piezoelectric response of Pb(ZrxTi 1-x)O3 at the morphotropic phase boundary: Role of elastic instability - Singh A.K.; Mishra S.K.; Ragini; Pandey D.; Yoon S.; Baik S.; Shin N. (My University, 2025)
Temperature dependent structural changes in a nearly pure monoclinic phase composition (x=0.525) of Pb (Zrx Ti1-x) O3 (PZT) have been investigated using Rietveld analysis of high-resolution synchrotron powder x-ray diffraction data and correlated with changes in the dielectric constant and planar electromechanical coupling coefficient. Our results show that the intrinsic piezoelectric response of the tetragonal phase of PZT is higher than that of the monoclinic phase. It is also shown that the high piezoelectric response of PZT may be linked with an anomalous softening of the elastic modulus (1 S11E) of the tetragonal compositions closest to the morphotropic phase boundary. © 2008 American Institute of Physics.